The Degree of Availability of Skills of Knowledge Economy among Students at Faculty of Social Sciences at AL Imam Mohamed Ibn Saud Islamic University from the perspectives of Faculty Members and students - Ramadan, Essam (Jordan Journal of Educational Sciences, 2015)
The objectives of the present study are to recognize the availability of skills of Knowledge Economy among students at the faculty of Social Sciences at AL-Imam Mohamed Ibn Saud Islamic University from the perspective of faculty members and students, and to recognize the effect of some variables on the sample of the study in determining the extent of skills of knowledge Economy among students. The study made use of the survey’s descriptive method through a questionnaire which included 32 items and was conducted to random sample of (77) faculty members and (299) students. The results of the study indicated that the skills of knowledge economy among students were available at medium degree for most dimensions of the questionnaire and the total score from the faculty members point of view, whereas the extent was high from the student’s point of view, The variables of cooperation and team work and efficient treatment skills were in the first and the second rank from the sample point of view. The study results showed statistical differences at 0, 05 among the means of sample of the study according to variables of position rank, experience of the faculty members and variables of school level for the students’ sample, while there were no significant differences amond students according their cumulative rate